Respuesta :

Answer:

p=1                                  p = -5/3

Step-by-step explanation:

1-|3p+1|=-3

Subtract 1 from each side

1-|3p+1| -1=-3-1

-|3p+1|=-4

Divide by -1

|3p+1|=4

The absolute value has two solutions one positive and one negative

3p+1 = 4            3p+1 = -4

Subtract 1 from each side

3p+1-1 = 4-1            3p+1-1 = -4-1

3p = 3                         3p = -5

Divide by 3

3p/3 = 3/3                    3p/3 = -5/3

p=1                                  p = -5/3

Answer:

p=-5/3,1

Step-by-step explanation:

Subtract 11 from both sides.

-|3p+1|=-3-1

−∣3p+1∣=−3−1

2 Simplify  -3-1−3−1  to  -4−4.

-|3p+1|=-4

−∣3p+1∣=−4

3 Multiply both sides by -1−1.

|3p+1|=4

∣3p+1∣=4

4 Break down the problem into these 2 equations.

3p+1=4

3p+1=4

-(3p+1)=4

−(3p+1)=4

5 Solve the 1st equation: 3p+1=43p+1=4.

p=1

p=1

6 Solve the 2nd equation: -(3p+1)=4−(3p+1)=4.

p=-\frac{5}{3}

p=−  

3

5

 

7 Collect all solutions.

p=-\frac{5}{3},1

p=−  

3

5

,1